A facility without its own territory - Straub, Edwina, author; Lundberg, Thomas R., advisor; Coronel, Patricia D., committee member; Ryan, Ajean Lee, committee member; Sparks, Diane, committee member (Colorado State University. Libraries, 2011)
Dipping into the reservoir of tacit knowledge, the phenomenon in art that is created through the "knowing of that" or embodied knowledge. The integration of experience and perception is where the motivations of my art making comes from. It is through the manipulation of fiber that I am able to transform its essence into something extraordinary. Through the process of dyeing, sewing and cutting I create patterns in space. Through the integration of their shadows into the artwork, I create the ephemeral character of my art. The hand-cut modules are sewn in a grid. Through the full integration of the grid into the artwork, in part as scaffold and in part as element of the artwork, I create a dynamic composition of movement.
Keywords: fiber-arts; ikat; installation; minimalism; shadow-line-drawing; Buddhism